Tackling offensive behaviour in Scottish football: A how (not) to guide to developing criminal justice policy? - McBride, Maureen (Criminology & criminal justice, 2022)
Since 2011, the issue of ‘sectarianism’ has dominated the Scottish political agenda as well as media and public discourse. The most high-profile aspect of the Scottish Government’s response to the problem was undoubtedly the Offensive Behaviour at Football (Scotland) Act 2012. This article is based on analysis of official documentation, speeches and media coverage relating to sectarianism and the Offensive Behaviour at Football and Threatening Communications Act since 2011. By tracing the Act’s journey from its introduction to its repeal in 2018, it challenges notions of a policymaking process built on consensus. It also casts doubt upon the Scottish Government’s claims of a socially progressive approach to criminal justice, as the behaviours of working-class youth around football have been increasingly problematised, criminalised and regulated. I argue that the Act highlights the need for an ongoing critique of the direction of criminal justice in Scotland and demonstrates the consequences of knee-jerk responses to complex social problems, which has relevance beyond the Scottish context.